Emerging applications of nanotechnology in context to immunology: A comprehensive review - Mobeen, Hifsa; Safdar, Muhammad; Fatima, Asma; Afzal, Samia; Zaman, Hassan; Mehdi, Zuhair (Frontiers in Bioengineering and Biotechnology, 2022)
Numerous benefits of nanotechnology are available in many scientific domains. In this sense, nanoparticles serve as the fundamental foundation of nanotechnology. Recent developments in nanotechnology have demonstrated that nanoparticles have enormous promise for use in almost every field of life sciences. Nanoscience and nanotechnology use the distinctive characteristics of tiny nanoparticles (NPs) for various purposes in electronics, fabrics, cosmetics, biopharmaceutical industries, and medicines. The exclusive physical, chemical, and biological characteristics of nanoparticles prompt different immune responses in the body. Nanoparticles are believed to have strong potential for the development of advanced adjuvants, cytokines, vaccines, drugs, immunotherapies, and theranostic applications for the treatment of targeted bacterial, fungal, viral, and allergic diseases and removal of the tumor with minimal toxicity as compared to to macro and microstructures. This review highlights the medical and non-medical applications with a detailed discussion on enhanced and targeted natural and acquired immunity against pathogens provoked by nanoparticles. The immunological aspects of the nanotechnology field are beyond the scope of this Review. However, we provide updated data that will explore novel theragnostic immunological applications of nanotechnology for better and immediate treatment.